The study of the lower limb entheses in the Neanderthal sample from El Sidrón (Asturias, Spain): How much musculoskeletal variability did Neanderthals accumulate?. Issue 141 (April 2020) - Belcastro, Maria Giovanna; Mariotti, Valentina; Pietrobelli, Annalisa; Sorrentino, Rita; García-Tabernero, Antonio; Estalrrich, Almudena; Rosas, Antonio
Abstract: Entheses have rarely been systematically studied in the field of human evolution. However, the investigation of their morphological variability (e.g., robusticity) could provide new insight into their evolutionary significance in the European Neanderthal populations. The aim of this work is to study the entheses and joint features of the lower limbs of El Sidrón Neanderthals (Spain; 49 ka), using standardized scoring methods developed on modern samples. Paleobiology, growth, and development of both juveniles and adults from El Sidrón are studied and compared with those of Krapina Neanderthals (Croatia, 130 ka) and extant humans. The morphological patterns of the gluteus maximus and vastus intermedius entheses in El Sidrón, Krapina, and modern humans differ from one another. Both Neanderthal groups show a definite enthesis design for the gluteus maximus, with little intrapopulation variability with respect to modern humans, who are characterized by a wider range of morphological variability. The gluteus maximus enthesis in the El Sidrón sample shows the osseous features of fibrous entheses, as in modern humans, whereas the Krapina sample shows the aspects of fibrocartilaginous ones. The morphology and anatomical pattern of this enthesis has already been established during growth in all three human groups. One of two and three of five adult femurs from El Sidrón and from Krapina, respectively, show the imprint of the vastus intermedius, which is absent among juveniles from those Neanderthal samples and in modern samples. The scant intrapopulation and the high interpopulation variability in the two Neanderthal samples is likely due to a long-term history of small, isolated populations with high levels of inbreeding, who also lived in different ecological conditions. The comparison of different anatomical entheseal patterns (fibrous vs. fibrocartilaginous) in the Neanderthals and modern humans provides additional elements in the discussion of their functional and genetic origin.